ANALISIS DINAMIS KETERKAITAN VARIABEL YANG MEMPENGARUHI NERACA TRANSAKSI BERJALAN INDONESIA TAHUN 2012 - Winta Ratna Sari (Universitas Negeri Medan, 2012)
This study was to analyze the contribution rate (the rupiah against the U.S. dollar), Libor Interest Rate, Inflation and Output Growth (GDP) of the current account balance in Indonesia. The data used in this study secondary data is sourced from Indonesia Financial Statistics. The data used is the data quarterly from the first quarter of 2000 up to 2010 fourth quarter. The results of the estimated Vector Autoregression (VAR) indicates that there is a relationship between the Current Account, Exchange Rate, Libor Interest Rate, Inflation and GDP at lag t-1. Impulse response function of the stability of the first note that all variables are in the long run that is over 5 years and tend to be stable. This means that in the short term variables that are used do not provide a meaningful contribution in the long term but will mutually contribute to each other. Variance Decomposition Based on these results, it is known that all variables contributed to the Current Account, but his greatest contribution is of the variable itself, this means that the current account tends to a variable receiving contributions rather than giving contributions